Sparkes, Rev. North River. Photograph of man, woman, and girl. - Sparkes, Rev.
Photo of Richard Atkins - Daughter Johanna Atkins - Wife Sarah Frances (always called Fanny) Fillier Atkins. This is parents of Florence Atkins great-grandparents of John Sparkes, Grand-Parents of Jean Bradbury